(untitled) (Security Dialogues, 2025)
The purpose of this paper is to identify the key security risks in the area of the Western Balkans, which are actually the common denominator in attempts at cooperation, coordination and integration in the field of creating defense and security policies, on regional and national level. Apart from the identification of security risks that determine the viability of Western Balkan actors, the fact that it is a region that is not fully integrated within the NATO defense and security infrastructure, partial integration will be used as a variable in the analysis of cooperation opportunities, in the political and contractual context. Finally, the capacities of regional cooperation in the field of security, determined by bilateral and regional agreement frameworks, will be presented. The contribution of this work in a scientific sense will be the answer to the question of how much the potential joint action of small states in the face of modern security risks affects the process of creating security sustainability at the individual (state) level, as the ultimate goal in understanding national interests.